Globalization : neoliberal challenge, radical responses - Went, Robert, 1955- (Pluto Press with the International Institute for Research and Education (IIRE), 2000)
In clear and concise terms, Robert Went demythologises globalization. Putting globalization into a historical perspective, Went convincingly demonstrates that it is not an unavoidable process, but one that the Left can successfully mobilise against.